STUDENTS’ PERCEPTION ON THE USE OF NHK CHANNEL IN LEARNING VOCABULARY - Multazam Abubakar; Jusnaeni (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2022)
This research aims at investigating the perception of the third-grade students on learning vocabulary through NHK channel at Madrasah Aliyah Masembo Maros. The method of this research was quantitative descriptive method. The population was all the students of the third grade in Madrasah Aliyah Ainus Syamsy Masembo Maros that consisted of 50 students. The samples were selected purposively, that were those who already watched NHK channel that consisted of 14 students. The data were collected through questionnaires. The data were analyzed by looking for the means score and intervals to classify them. The result indicated that there was a positive perception of watching NHK channel on students’ learning. It was proved by the mean score of total number of all of the questions as 56,6 which was classified as very high. Therefore, it is concluded that learning vocabulary through NHK Channel has good response from third grade students of Madrasah Aliyah Ainus Syamsy Masembo Maros or in the other words the use of media as learning tool such as NHK channel can help students in learning vocabulary